Significance of the Pathologic Findings in Implantation Biopsies for Kidney Allografts Survival - Trailin, A. V.; Nykonenko, T. N.; Ostapenko, T. I.; Vildanov, S. R.; Nykonenko, O. S.; Вільданов, Сергій Ренатович; Никоненко, Олександр Семенович (My University, 2019)
Background: There is no consistent association between individual histological lesions and composite scores in donor kidney biopsy and transplant outcomes. Objective: To evaluate which acute or chronic individual histological lesions and composite scores in donor kidney were associated with graft survival in the recipient. Methods: We investigated the association of individual histological lesions and 8 composite scoring systems in implantation biopsies of cadaveric (n=101) and living (n=29) kidneys with 5-year death-censored graft survival. Results: We found a high frequency of chronic lesions in donor kidneys, mostly associated with arteriosclerosis, and less dependent from donor age. Acute, chronic, and total Banff scores for post-transplant biopsies, chronic and total Banff scores for pre-implant biopsies, donor damage score and chronic damage score predicted death-censored graft loss. However, only chronic and total Banff-scores had significant effects in multivariate model. Chronic pre-implant and total post-transplant Banff scores demonstrated the highest area under the curve (AUC) of 0.722 and 0.717, respectively. Among individual lesions, glomerulosclerosis ≥20%, interstitial inflammation >0, arteriosclerosis =3, arteriolar hyalinosis >0, and interstitial fibrosis >0, assessed with Banff-grading criteria, were associated with lower allograft survival. We created the Donor Kidney Damage Index (DKDI), by summing regression coefficients for these lesions, which yielded the AUC of 0.747. When combined with retransplantation, cold ischemia time and acute rejection, DKDI, chronic pre-implant and total post-transplant Banff scores further improved their predictive accuracy, yielding AUCs of 0.842, 0.807, and 0.802, respectively. Conclusion: DKDI, chronic pre-implant and total post-transplant Banff scores alone and combined with clinical variables may facilitate decision making in post-transplant period.
Keywords: Implantation biopsy histology; Individual and composite histological scores; Kidney allograft survival